Standard and innovative options in the treatment of insulin resistance - Jakub Metelski; Katarzyna Krauze-Kuc; Aleksandra Metelska; Dominika Sereda; Hubert Nieścior (Kazimierz Wielki University, 2022)
Introduction and purpose  Insulin resistance is a state of decreased tissue sensitivity to insulin, despite normal or elevated levels of this hormone in the blood serum. People with insulin resistance for a long time do not show symptoms, which makes it particularly difficult to detect and treat in early stages. It mainly leads to impaired glucose homeostasis and the development of type 2 diabetes, which contributes to the exacerbation of the global problem that diabetes has become. This results in the search for innovative therapies that will help combat insulin resistance better and better. The purpose of this study is to highlight the complexity of the IR and review the current literature for non-pharmacological and pharmacological possibilities of treatment  for insulin resistance.  Description of the state of knowledge  Due to the increase in obesity and the metabolic syndrome, the number of people suffering from insulin resistance is constantly increasing.  In modern times, there are various diagnostic and therapeutic methods that affect the course of insulin resistance. Early detection and introduction of appropriate therapy become the main goal in preventing complications that may occur in the course of this disease.   Summary Treatment methods for insulin resistance can be divided into two groups - non-pharmacological and pharmacological. Both of them are often used together in the form of combination therapy aimed at obtaining the best results in the treatment of insulin resistance. For people for whom known therapies do not work, researches for new treatments is becoming a hope.